2016
DOI: 10.1111/1365-2478.12449
|View full text |Cite
|
Sign up to set email alerts
|

Micro X‐Ray computed tomography imaging and ultrasonic velocity measurements in tetrahydrofuran‐hydrate‐bearing sediments

Abstract: Naturally occurring gas hydrates contain significant amounts of natural gas that might be produced as an energy resource in the foreseeable future. Thus, it is necessary to understand the pore‐space characteristics of hydrate reservoirs, particularly the pore‐scale distribution of the hydrate and its interaction with the sediment. Four end‐member models for hydrate distribution in the pore space are pore filling, sediment‐frame component, envelope cementing, and contact cementing. The goal of this study is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 31 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…Different mechanisms contribute to different hydrate morphologies. Various researchers have explored the pore habit of the hydrate in the synthesized HBS using the X-ray computed tomography (CT) technique, which enables non-destructive 3-D visualization of porous media (Chaouachi et al 2015;Li et al 2019b;Mahabadi et al 2016b;Schindler et al 2016;Seol et al 2019;Takeya et al 2007;Wu et al 2020aWu et al , 2020bYang et al 2015). This technique provides an insight into hydrate nucleation, growth, and distribution in the HBS.…”
Section: Synthesized Hbsmentioning
confidence: 99%
“…Different mechanisms contribute to different hydrate morphologies. Various researchers have explored the pore habit of the hydrate in the synthesized HBS using the X-ray computed tomography (CT) technique, which enables non-destructive 3-D visualization of porous media (Chaouachi et al 2015;Li et al 2019b;Mahabadi et al 2016b;Schindler et al 2016;Seol et al 2019;Takeya et al 2007;Wu et al 2020aWu et al , 2020bYang et al 2015). This technique provides an insight into hydrate nucleation, growth, and distribution in the HBS.…”
Section: Synthesized Hbsmentioning
confidence: 99%
“…Experimental studies on characterization of tetrahydrofuran hydrates were carried out by Pohl et al [40]. On the other hand, pore space characteriza-tion using ultrasonic waves was performed by Schindler et al [41]. Recently, a more novel method of detecting natural gas hydrates using ultrasonic assisted technique was developed by Li et al [42].…”
Section: Ultrasonic Wavesmentioning
confidence: 99%
“…3. As discussed earlier, the use of electromagnetic radiation for enhanced oil recovery is well known [35,41,42]. However, application of electromagnetic radiation for gas recovery from natural gas hydrate reservoirs is still largely unexplored territory.…”
Section: Rf-based Hydrate Dissociationmentioning
confidence: 99%
See 1 more Smart Citation
“…The micro X‐ray CT and ultrasonic velocity measurements were used to obtain the hydrate distribution information in the pore space of synthetic deposits (glass beads) by Schindler et al The results showed that tetrahydrofuran hydrate was formed in the pore space. To visually observe the occurrence mode of hydrate, the 40 wt% tetrahydrofuran and 25 wt% barium chloride were used in the artificial sand with a particle size of 500 μm.…”
Section: Identifying the Occurrence Mode Of Hydrate In Sedimentsmentioning
confidence: 99%